STRATEGI GURU DALAM MENCEGAH DAN MENANGANI PERILAKU BULLYING PADA ANAK DAN REMAJA - Pratiwi, Selvi Anggia; Febrianti, Nike; Sari, Yuli Indah; Puriani, Risma Anita; Novirson, Rizki (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
The background of this study is based on the high number of bullying cases in schools that can have a negative impact on students' psychological and social development. The purpose of this study is to explore various strategies that can be carried out by teachers in an effort to prevent and handle bullying behavior among children and adolescents. The method used is content analysis, which involves data identification and analysis. The sample used was articles published on googlescholar and researcghate ranging from 2015-2024. The results revealed that bullying is a negative behavior that reflects violent and discriminatory actions, which can arise due to differences in social status, lifestyle, and interests between students. The findings highlight the importance of the role of teachers as a key component in the education system to prevent and address bullying behavior in the school environment. Training and workshops for teachers are also needed to prevent and address bullying behavior and also to improve communication skills and appropriate interventions.